2022
DOI: 10.4103/2221-1691.350182
|View full text |Cite
|
Sign up to set email alerts
|

Human Wharton's jelly mesenchymal stem cells inhibit cytokine storm in acute respiratory distress syndrome in a rat model

Abstract: Objective: To evaluate the potential effect of human Wharton's jelly mesenchymal stem cells (hWJMSCs) on acute respiratory distress syndrome in lipopolysaccharide (LPS)-induced rats. Methods: The hWJMSCs (5×104/mL, 5×105/mL, 5×106/mL) were administered to rats on day 1 and day 8 after being induced by LPS (5 mg/kg body weight). TNF-α levels in the lung and IL- 18 and IL-1β levels in the serum were measured using ELISA. In addition, caspase-1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In our previous study, hWJMSCs were found to decrease lung inflammation in ARDS rats through decreasing IL-18 and IL-1β, and consequently suppressing the NFκB cascade. 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, hWJMSCs were found to decrease lung inflammation in ARDS rats through decreasing IL-18 and IL-1β, and consequently suppressing the NFκB cascade. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study has indicated that hWJMSCs treatment in animals lungs upregulates FGF-7, thereby inhibiting apoptosis. 1 , 18 , 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lungs were then snap-frozen in liquid nitrogen and stored at -80°C until used. Lungs were stored and dissected for histopathological analysis and immunohisto-chemistry [18][19][20].…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The sample analysis was according to the protocol of manufacture with a modified method. The absorbance was read triplicate at 450 nm (Multiskan GO, Thermo Scientific) [18,20].…”
Section: Quantification Of Lung Il-18 Il-12 and Serum Il-1β Tnf-αmentioning
confidence: 99%